KANDUNGAN ACID DETERGENT FIBER (ADF) DAN NEUTRAL DETERGENT FIBER (NDF) PADA RUMPUT Brachiaria humidicola PADA UMUR DEFOLIASI BERBEDA - Gusti Khairun Ni'mah; Muhammad Syarif Djaya (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
This study aims to determine the content of neutral detergent fibre (NDF) and acid detergent fibre (ADF) of Brachiaria humidicola grass at different depoliation ages. This research is a pure experiment using the Completely Randomized Design (CRD) method with three treatments (40 days, 50 days and 60 days) and three replications. The results showed that depoliation age had no significant effect (P>0.05) on the NDF and ADF content of Brachiaria humidicola grass with NDF values ranging from 64.20% to 65.49%, while ADF values ranged from 36.75% to 43.99%.